2016
DOI: 10.1891/0889-8391.30.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Mindfulness, Compassion, and Loving Kindness Program on Chronic Depression: A Pilot Within-Subjects Wait-List Controlled Trial

Abstract: In this pilot study, N = 11 patients suffering from chronic depression were treated in a 12-week group program consisting of basic mindfulness exercises from Mindfulness-Based Cognitive Therapy and compassion exercises from Compassion Focused Therapy and Loving Kindness Meditation. In a 3-month waiting period prior to treatment, depression symptoms both in self-report and clinician rating did not change significantly. After treatment, depression severity was significantly reduced. After a 3-month follow-up, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Interestingly, this change was predicted by pre‐post changes in mindfulness, but not self‐compassion—however, after controlling for mindfulness, self‐compassion was the only significant predictor of depression and anxiety. In addition, in a small pilot study, Graser, Höfling, Weßlau, Mendes, and Stangier () evaluated a 12‐week mindfulness, compassion, and LKM group intervention for patients suffering from chronic depression and found no change in self‐compassion. However, the authors found significant reductions in depression severity relative to 3‐month baseline measures, as well as a significant effect for improvements in acceptance, suppression, and self‐focused rumination between pre‐therapy and 3‐month follow‐up.…”
Section: Self‐compassion and Cognitive Emotion Regulationmentioning
confidence: 99%
“…Interestingly, this change was predicted by pre‐post changes in mindfulness, but not self‐compassion—however, after controlling for mindfulness, self‐compassion was the only significant predictor of depression and anxiety. In addition, in a small pilot study, Graser, Höfling, Weßlau, Mendes, and Stangier () evaluated a 12‐week mindfulness, compassion, and LKM group intervention for patients suffering from chronic depression and found no change in self‐compassion. However, the authors found significant reductions in depression severity relative to 3‐month baseline measures, as well as a significant effect for improvements in acceptance, suppression, and self‐focused rumination between pre‐therapy and 3‐month follow‐up.…”
Section: Self‐compassion and Cognitive Emotion Regulationmentioning
confidence: 99%
“…Previous within-group design studies [35, 38] showed moderate to large pre-post effect strengths of the group meditation program. The expected effect size for wait-list controlled studies cannot be derived from within-group design studies.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention also involves the development of an accepting attitude towards negative emotions and cognitions [65], as well as actions involving benevolence to self and others [29]. The practice of combining these interventions has been done informally by our work group in several cases of chronically depressed patients from our pilot studies [35, 38] who had completed the studies but required additional treatment after termination of the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations